2012
DOI: 10.1021/jf3012807
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Single Soybean Seed Attributes by Near-Infrared Technologies. A Comparative Study

Abstract: Four near-infrared spectrophotometers, and their associated spectral collection methods, were tested and compared for measuring three soybean single-seed attributes: weight (g), protein (%), and oil (%). Using partial least-squares (PLS) and four preprocessing methods, the attribute that was significantly most easily predicted was seed weight (RPD > 3 on average) and protein the least. The performance of all instruments differed from each other. Performances for oil and protein predictions were correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“… Agelet et al (2012) reported that working at shorter wavelengths, i.e. 900–1650 nm, did not give significantly different results in terms of prediction performance.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“… Agelet et al (2012) reported that working at shorter wavelengths, i.e. 900–1650 nm, did not give significantly different results in terms of prediction performance.…”
Section: Resultsmentioning
confidence: 98%
“…Previous literature dealing with NIR prediction of small grain weight reported slightly better performances for soybean kernel weight prediction, i.e. R 2 = 0.77–0.91 depending on the spectral pre-treatment, wavelength region selected and instrumentation used ( Agelet et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of compression damage detection results show that the best UVE-LS-SVM model had the highest RPD, at 2.139, indicating that the model is usable for screening [49]. Besides the detection of the damage level, the discrimination of the damaged fruit is also important for the industry.…”
Section: Discrimination Of Damaged Fruitmentioning
confidence: 99%